تقييم معلومات القابلات حول الاستراتيجيات المستخدمة في الوقاية و تدبير النزيف بعد الولادة - مصطفى, نسرين (Latakia University Journal -Medical Sciences Series, 2017)
يعد النزيف بعد الولادة (PPH- (Postpartum Hemorrhage أحد أهم المضاعفات التي تحدث بعد الولادة الطبيعية أو القيصرية, و يمثل حوالي ربع وفيات الأمهات حول العالم. و تلعب القابلات الدور الأساس في الوقاية من النزيف بعد الولادة. لذا يهدف هذا البحث إلى تقييم معلومات القابلات حول الاستراتيجيات المستخدمة في الوقاية من النزيف بعد الولادة وتدبيره. حيث شملت عينة البحث جميع القابلات الموجودات في قسم التوليد في مشفى الأسد الجامعي و مشفى الأطفال و التوليد و مشفى تشرين الجامعي في مدينة اللاذقية. و جمعت البيانات باستخدام استمارة استبيان مطورة من قبل الباحث. وقد أظهرت النتائج أن مستوى المعرفة فيما يتعلق بالاستراتيجيات المستخدمة في الوقاية و تدبير النزيف بعد الولادة عند (60 %) من القابلات كان "غير ملائم". وبينت وجود علاقة عكسية هامة إحصائياً (P=0.006) بين عمر القابلات ومستوى المعرفة لديهن. وعلاقة عكسية هامة إحصائياً أيضاً بين عدد سنوات الخبرة لدى القابلات ومستوى المعرفة لديهن (P=0.01). لذلك نقترح إجراء دورات تدريبية ومحاضرات تثقيفية للقابلات فيما يتعلق بالاستراتيجيات المستخدمة في الوقاية من النزيف بعد الولادة وتدبيره، و ضرورة تقييم معلومات القابلات حول الوقاية وتدبير النزيف بعد الولادة بشكل دوري ومستمر.The bleeding after delivery (Postpartum Hemorrhage-PPH) is the most important complications that occur after a natural or cesarean delivery, and represents about a quarter of maternal mortality around the world. Midwives play a basis role in prevention of bleeding after birth. So This research aims to evaluate the knowledge of midwives about using strategies to prevention and management the bleeding after delivery. Its sample included all midwives in obstetrics departments in Alasad University, Children and Obstetric, and Tishreen University Hospital all in Lattakia city. Data were collected using a questionnaire developed by researcher. The results according to strategies used in prevention and management of bleeding after delivery showed that 60% of the level of knowledge of midwives were "inappropriate". There were significant inverse relationship (P = 0.006) between ages of midwives and level of knowledge. Also showed a significant inverse relationship between number of years of experience with the midwives and level of knowledge (P = 0.01). So we suggest conducting training sessions and educational lectures for midwives with respect to the strategies used in prevention and management of bleeding after delivery, and must evaluate the midwives information about prevention and management of bleeding after delivery periodically and continuously.